Resolving power of scintillation panels based on zinc selenide - Litichevskyi, V.; Galkin, S.; Lalaiants, O.; Voronkin, E.; Mahota, S.; Breslavskiy, I. (Functional Materials, 2012)
This work presents some characteristics of experimental samples of flexible scintillation panels made on the basis of fine-powders of zinc selenide scintillator. The purpose of the work was to determine the resolving power of dispersed scintillation panels based on ZnSe(Te) and to clarify the field of their application in X-ray technique. In the course of studying the dependences of the resolving power of scintillation panels based on ZnSe(Te) on the powder particles size and thickness of the panels were discovered. The data on the dependences of the light output on the panel thickness and particle size of the scintillator in the samples in the thickness range of 0.1-1 mm are presented. X-ray images of different test objects obtained using scintillation panels based on zinc selenide are shown. Three ranges of the particles dispersion were investigated: the first — 25-40 µm, the second — 40-120 µm, and the third — 120-200 µm. It was revealed that the resolving power was 5, 3 and 2.5 lp/mm for the each range of dispersion.